The Effects Of Temporal Delay On The Performance Of An Electro-optic Q-switched Nd:YAG Laser - Nur Athirah Mohd Taib; Noriah Bidin; M. Fakaruddin Sidi Ahmad; Nurul Nadia Adnan; Ganesan Krishnan; Sulaiman Wadi Harun (Optoelectronics And Advanced Materials-Rapid Communications, 2024)
Volume: 9 No. 5-6 (Page: 724 - 729)